2022
DOI: 10.1002/mabi.202200019
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Hydrogel Scaffolds with Copper Peptide‐Functionalized RADA16 Nanofiber Improve Wound Healing in Diabetes

Abstract: Wound healing in diabetes is retarded by the dysfunctional local microenvironment. Although there are many studies using hydrogels as substitutes for natural extracellular matrices (ECMs), hydrogels that can mimic both the structure and functions of natural ECM remain a challenge. Self‐assembling peptide RADA16 nanofiber has distinct advantages to provide a biomimetic extracellular matrix nanofiber structure. However, it still lacks biological cues to promote angiogenesis that is of vital significance for diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Recently, hydrogel-based dressings have shown powerful effects in accelerating trauma-repairing in animal experiments and clinical trials [ 15 , 18 , 19 ]. Promising results have been shown by SAP hydrogels when promoting the regenerative repair of nerve injuries [ 20 ], cartilage regeneration [ 21 ], and skin wound healing [ 22 ], owing to the unique advantage of mimicking natural ECM. However, the ability of SAP hydrogel therapy alone to treat diabetic wounds still needs to be explored.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, hydrogel-based dressings have shown powerful effects in accelerating trauma-repairing in animal experiments and clinical trials [ 15 , 18 , 19 ]. Promising results have been shown by SAP hydrogels when promoting the regenerative repair of nerve injuries [ 20 ], cartilage regeneration [ 21 ], and skin wound healing [ 22 ], owing to the unique advantage of mimicking natural ECM. However, the ability of SAP hydrogel therapy alone to treat diabetic wounds still needs to be explored.…”
Section: Resultsmentioning
confidence: 99%
“…For example, RADA16 peptide nanofiber has advantages in providing an ECM-like environment for promoting cell attachment and proliferation. Utilization of this scaffold in combination with a copper peptide glycyl-histidyl-lysine (GHK) functionalized the system to also promote angiogenesis and accelerate diabetic wound closure . The design and integration of bioactive peptides into scaffold materials should take into consideration the application of the material, tissue type, and presentation of epitopes presented in the peptide network.…”
Section: Moving Forwardmentioning
confidence: 99%
“…They demonstrated that the peptide significantly reduced bleeding time and reduced bleeding volume 119 . Yang et al prepared a copper peptide-functionalized RADA16 system that was used to study a diabetic mouse model to effectively accelerate the processes of wound closure and tissue repair 26 . Self-assembled peptide sequences can be potentially used to realize hemostasis, although some persistent disadvantages hinder their clinical applications.…”
Section: Introductionmentioning
confidence: 99%